Differences in Self-Concept of Students from Intact Families And Non-Intact Families - Monika Veronika; Afdal Afdal (Jurnal Aplikasi IPTEK Indonesia, 2019)
This research is motivated by the phenomenon of the number of students from non-intact families lacking self-confidence, thus causing him to be less able to see himself positively. The purpose of this study is to see the difference in self-concept of students from intact families and families not intact. This research is a quantitative type of research with a comparative descriptive method. The population in this study were all students of SMP 25 Padang in the 2018/2019 academic year, totaling 744 students. The total sample of 260 students (150 students from intact families and 110 students from non-intact families) was selected using the Stratified Random Sampling technique. The research instrument used was a Likert scale questionnaire. Data were analyzed by percentage formula technique and formula t test with the help of SPSS for Windows 16. 0. The results revealed that (1) self-concept of students from intact families were in the high category (2) self-concept of students from non-intact families in the category quite high, and (3) there is a significant difference between the self-concept of students from intact families and non-intact families with a significant level of 0,000. Based on the results of the study it was suggested to counselors to be able to provide guidance and counseling services, information services, individual counseling services, group guidance services and group counseling services to students from non-intact families, in order to help students realize positive self-concepts.